1977
DOI: 10.1111/j.1365-2265.1977.tb01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Androgens in Women With Hyperprolactinaemic Amenorrhoes

Abstract: Cortisol, androstenedione, testosterone, dehydroepiandrosterone sulphate (DHAS) and free dehydroepiandrosterone (DHA) were measured in plasma of ten women affected by amenorrhoea with hyperprolactinaemia and eleven women affected by secondary hypothalamic amenorrhoea; twelve normal women at the second day of the menstrual cycle were used as controls. All subjects were hospitalized and 17-ketosteroids, 17OH-corticosteroids and total dehydroepiandrosterone were also measured in urine. Plasma DHAS was increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
2

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(36 citation statements)
references
References 14 publications
3
30
1
2
Order By: Relevance
“…The elevated levels of DHEA-S in particular confirm our previous report (3) and those of others (1,2,4), but the finding of lower total T, DHT, and Adiol is at variance with other reports (8)(9)(10). A significant finding in this study is that baseline serum SHBG-BC is decreased while CBG-BC is normal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The elevated levels of DHEA-S in particular confirm our previous report (3) and those of others (1,2,4), but the finding of lower total T, DHT, and Adiol is at variance with other reports (8)(9)(10). A significant finding in this study is that baseline serum SHBG-BC is decreased while CBG-BC is normal.…”
Section: Discussionsupporting
confidence: 93%
“…Other androgens, such as testosterone (T) and androstenedione (Adione), have been reported to be normal (4,8,9). In these patients, the elevated DHEA-S levels may be explained by the finding of a normal MCR (10,11) but an increased production rate (PR) of DHEA-S (11).…”
mentioning
confidence: 96%
“…Serum FSH and prolactin also display changes which are different in the two sexes, and herald the onset of puberty ( 3 ) . The interaction of prolactin and the adrenal cortex in puberty is possible, because elevated prolactin production leads to elevated serum DHEA, which returns to normal along with the normalization of serum prolactin (5,6,19). However, the small physiological changes of serum prolactin in infants and during the years prior to puberty, especially in boys ( l ) , make it unlikely that prolactin alone is of importance in the initiation of puberty.…”
Section: Discussionmentioning
confidence: 98%
“…2' In view of the stimulation exerted by prolactin on adrenal function, in particular on the production of androgens (of maternal and mainly fetal origin) that serve as precursors for placental oestrogen synthesis during pregnancy, the effect of bromocriptine on the production of dehydroepiandrosterone sulphate (DHAS) was studied by several groups. Bassi et al 3 showed that women with hyperprolactinaemic amenorrhoea had significantly elevated plasma levels of DHAS, which were reduced by bromocriptine, together with those of prolactin; basal plasma cortisol was normal, as were plasma androstenedione and testosterone and urinary 17-ketosteroids and 17-hydroxycorticosteroids. In other words, prolactin appeared to stimulate the production of DHAS.…”
Section: The Endocrinology Of Bromocriptine-facilitated Pregnanciesmentioning
confidence: 97%